Digital technology applications on indoor environment quality : a research thesis presented in partial fulfilment of the requirements for the degree of Master of Construction, Massey University, New Zealand - Liao, Ruochen (Massey University, 2021)
Under the background of understanding various digital technologies, the aim of this research is to investigate the current application of digital technology in indoor environment quality. Indoor environment quality is closely related to residents' health. In modern times, digital technologies have become more sophisticated and widely used. But research on the application of digital technology to indoor environment quality is relatively limited. This research examines the results using a systematic literature review to develop a conceptual framework around the current digital technology situation, indoor environment factors that can be affected by digital technology, and digital technology application methods. This research has proven that 7 digital technologies, such as BIM, IoT, AR, VR, smart sensor, tridimensional laser scanning, and HDRI can be used to monitor, control, evaluate building performance, and assess occupant preferences in relation to indoor air quality, indoor thermal comfort, and other factors related to indoor environment quality. Moreover, it has contributed to providing convenient monitoring, maintaining the room in a healthy environment in real-time, as a reference for designers to achieve an optimal design, and so forth. However, the negative factors such as the cost of digital technology and energy consumption are not mentioned in this research, and the types of indoor spaces involved are also relatively wide, which are the limitations.
Figure 1 (Abdul Majeebu, 2019 Fig 1) is re-used under a Creative Commons Attribution 3.0 Unported (CC BY 3.0) license.
Keywords: 330201 Automation and technology in building and construction